(untitled) (Pedagogy of Higher and Secondary Education, 2009)
The article considers the role of professional-aesthetic orientation and reflexion in the process of aesthetic outlook formation of future teachers it is proved that the availability of this orientation and the provision of reflexive guidance of the process of aesthetic outlook formation are pedagogical conditions of this outlook formation.